2017
DOI: 10.1063/1.4980060
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh refractive index sensitivity and tunable polarization switching via infrared plasmonic lattice modes

Abstract: We demonstrate tunable polarization-dependent infrared plasmonic lattice modes in the range of 1 to 1.7 μm in arrays of large gold nanodisks with a rectangle lattice structure. We show that when these arrays are exposed to air, their main mode appears around 1 μm. Under this condition, addition of chemicals leads to significant wavelength shifts in this mode, offering a refractive index sensitivity of about 795 nm/RIU (refractive index unit). Our results show that this process is accompanied by excitation of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…They demonstrated that narrow SLRs could be shifted from the visible (∼650 nm) through to the infrared (∼900 nm) range by altering the environment's refractive index. Gutha et al 235 confirmed that 2D arrays of large gold metallic nanodisks may have a greater sensitivity to changes in the superstrate's refractive index in the near IR region. The authors tuned the SLRs modes, using ultrathin layers of silicon, in the range from 1 to 1.7 μm and achieved a reasonably high refractive index sensitivity of ∼795 nm/RIU.…”
Section: Biosensing and Biorecognitionmentioning
confidence: 99%
“…They demonstrated that narrow SLRs could be shifted from the visible (∼650 nm) through to the infrared (∼900 nm) range by altering the environment's refractive index. Gutha et al 235 confirmed that 2D arrays of large gold metallic nanodisks may have a greater sensitivity to changes in the superstrate's refractive index in the near IR region. The authors tuned the SLRs modes, using ultrathin layers of silicon, in the range from 1 to 1.7 μm and achieved a reasonably high refractive index sensitivity of ∼795 nm/RIU.…”
Section: Biosensing and Biorecognitionmentioning
confidence: 99%
“…Metal nanoparticles (NPs) have been extensively adopted for light management in the visible spectrum. On metal NPs, localized surface plasmon resonance (LSPR) can be excited by incident lights and a strong evanescent electromagnetic (EM) field can be generated around the metal NPs within a short range of a few tens to a few hundreds of nanometers. , The LSPR frequency is determined by free electron concentration in the metal, with minor tunability by the size and shape of the metal NPs as well as the external surrounding media . An important result of the LSPR is the enhancement of EM field surrounding metal NPs from several times to tens of times. Therefore, this enhanced EM field can provide dramatically enhanced absorption to the photosensitizer layer, leading to an increased concentration of electron–hole pairs and thereby improved photoresponsivity. Typically, Ag and Au are two promising plasmonic materials for the application in the perovskite photodetector, as the LSPR frequency of Ag and Au could be tuned over the visible spectrum that matches the absorption spectrum of perovskite thin films.…”
Section: Introductionmentioning
confidence: 99%
“…A very recent study revealed that arrays of large gold nanodisks with a rectangle lattice structure can tune polarizationdependent plasmonic lattice modes, which is in principle based on the diffraction of light. 48 However, additional simulations of the array of dielectric dimers, which are not shown in this manuscript due to the lack of space, confirmed that the polarization switching in this study comes from the mode hybridizations of the excited electric and magnetic dipoles, rather than from the light diffraction.…”
mentioning
confidence: 49%